Integrating extended focused assessment with sonography for trauma (eFAST) in the initial assessment of severe trauma: Impact on the management of 756 patients. Issue 10 (October 2018) - Zieleskiewicz, Laurent; Fresco, Raphaelle; Duclos, Gary; Antonini, François; Mathieu, Calypso; Medam, Sophie; Vigne, Coralie; Poirier, Marion; Roche, Pierre-Hugues; Bouzat, Pierre; Kerbaul, François; Scemama, Ugo; et al.
Abstract: Background: Before total body computed tomography scan, an initial rapid imaging assessment should be conducted in the trauma bay. It generally includes a chest x-ray, pelvic x-ray, and an extended focused ultrasonography assessment for trauma. This initial imaging assessment has been poorly described since the increase in the use of ultrasound. Therefore, our study aimed to evaluate the diagnostic accuracy and therapeutic impact of this initial imaging work-up in severe trauma patients. A secondary aim was to assess the therapeutic impact of a chest x-ray according to the lung ultrasonography findings. Methods: Patients with severe trauma who were admitted directly to our level 1 trauma center were consecutively included in this retrospective single center study. The diagnostic accuracy, therapeutic impact, and appropriate decision rate were calculated according to the initial assessment results of the whole body computed tomography scan and surgery reports. Results: Among the 1315 trauma patients admitted, 756 were included in this research. Lung ultrasound showed a higher diagnostic accuracy for haemothorax and pneumothorax cases than the chest x-ray. Sensitivity and specificity of the abdominal ultrasound to detect intraperitoneal effusion were 70% and 96%, respectively. The initial assessment had a therapeutic impact in 76 (10%) of the patients, including 16 (2%) immediate laparotomies and 58 (7%) chest tube insertions. The pelvic x-ray had no therapeutic impact, and when the lung ultrasound was normal, the chest x-ray had a therapeutic impact of only 0.13%. Combining the chest x-ray and lung ultrasound allowed adequate management of all the pneumothorax and haemothorax cases. Only one of the 756 patients had initial management that was judged as inappropriate. This patient had a missed pelvic disjunction with active retroperitoneal bleeding, and underwent an inappropriate immediate laparotomy. Conclusions: In our cohort, the initial imaging assessment allowed appropriate decisions in 755 of 756 patients, with a global therapeutic impact of 10%. The pelvic x-ray had a minimal therapeutic impact, and in the patients with normal lung ultrasounds, the chest x-ray marginally affected the management of our patients. The potential consequences of abandoning systematic chest and pelvic x-rays should be investigated in future randomized prospective studies.